The Prone Position Improves the Oxygenation Status of Patients with COVID-19 (Systematic Review-Meta Analysis) - Rohmat Rohwandi; Hotma Rumahorbo; Linlin Lindayani; Susilawati Susilawati; Asep Badrujamaludin (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Hypoxemia in Corona Virus 19 patients requires supportive and rehabilitative treatment. PP is a technique that is considered to be safe for improving patient oxygenation. This review aimed to determine a cumulative effect of PP on oxygenation status in COVID-19 patients.The method used The search was carried out independently and systematically on the ProQuest, PubMed, Science Direct, Google Scholar and Semantic Scholar databases from January 2020, until June 2022.  Article screening was carried out through 3 stages: screening duplicate articles, titles and abstracts, and full-text screening by the expected criteria with preferred Items for PRISMA Standards. The quality assessment of the article uses the Joanna Briggs Institute (JBI) checklist form and the Review Manager software. The results A total of 323 articles were evaluated using an RCT or Quasi Experiment design with a control group. It was found that PP had an influence on changes in the value of the ROX index, PaO2/ FiO2 Ratio, SPO2, and SaO2 / FiO2 Ratio with p-value 0.05. Qualitatively, several positive results were obtained from the synthesis of each research. PP was assessed using a ventilation-perfusion matching mechanism in increasing oxygenation and preventing lung injuries.It is concluded that  PP was considered safe even though it caused side effects but it could still be done with good monitoring from health providers.